Cu (I) conductive coordination polymer material and preparation and application methods thereof

By using CuBr or CuI and pytrz to prepare Cu(I) conductive coordination polymer, forming a one-dimensional chain-shaped and double-stranded structure, the problem of insufficient conductivity of existing c-MOFs is solved, and efficient conductivity performance and good performance are achieved Thermal stability.

CN119390997APending Publication Date: 2025-02-07CHANGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411531475.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing conductive metal organic frames (c-MOFs) have shortcomings in conductivity and are difficult to achieve ideal conductivity, especially under high temperature conditions.

Method used

Cu(I) conductive coordination polymer is prepared by using CuBr or CuI and pytrz (3-(4H-1,2,4-triazol-4-yl)pyridine), forming a one-dimensional chain structure and a double-strand structure. Provides an effective charge transfer path.

Benefits of technology

It achieves efficient conductivity performance, and the conductivity is significantly improved at room temperature. Especially at 100℃, the conductivity further increases, with good thermal stability and broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390997A_ABST
    Figure CN119390997A_ABST
Patent Text Reader

Abstract

The invention relates to the field of photoelectric materials, in particular to a Cu (I) conductive coordination polymer material and a preparation and application method thereof. The material is obtained by reaction of pytrz and cuprous halide at room temperature, and pytrz is 3-(4H-1, 2, 4-triazole-4-yl) pyridine. According to the invention, two conductive coordination polymers with high stability are designed and synthesized, and the conductive coordination polymers have good thermal stability and small band gap. The temperature-related conductivity measured by the complex as a semiconductor and alternating current impedance is 2.18 * 10 < 4 > Scm < 1 > and 5.85 * 10 <-6 > Scm < 1 > at room temperature, the conductivity of the complex 1 and the conductivity of the complex 2 are 1.01 * 10 < 2 > Scm < 1 > and 8.76 * 10 <-5 > Scm < 1 > at 100 DEG C along with temperature rise, and the complex shows good conductivity performance and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photoelectric functional materials, and relates to a method for preparing a Cu(I) conductive coordination polymer material with high electrical conductivity. Background Art

[0002] Metal-organic frameworks (MOFs) are composed of organic ligands and inorganic nodes. They are porous crystalline materials with adjustable functions and tunable pore sizes, designable framework topologies, and high surface areas. Due to their excellent properties, they have attracted increasing attention in the fields of gas separation and adsorption, biomedicine, sensing, luminescence, energy storage, separation, and catalysis. The serious environmental crisis and the shortage of traditional fossil fuels have stimulated the urgent demand for renewable energy such as solar radiation and wind energy, as well as advanced storage technologies.

[0003] Conductive metal-organic frameworks (c-MOFs) are considered to be the most attractive candidates for electrochemical catalysis and energy storage due to their high surface area, which can provide appropriate space for electrochemical reactions and ion storage / transfer, such as electrocatalysis, energy storage, optoelectronic devices, chemiresistor sensors, and thermoelectrics, helping to advance modern electronic and energy technologies.

[0004] In order to exhibit ideal conductivity, MOFs must have sufficient carrier concentration and effective long-range charge transport pathways. The charge transport pathways in c-MOFs originate from their conjugated two-dimensional planar structures; their aromatic and conjugated structures allow charge delocalization, resulting in through-bond charge transport; and strong orbital interactions between two-dimensional layers promote through-space charge transport. The high conductivity of MOFs can be achieved by integrating conjugated planes or one-dimensional chains in the structure, which depends on the specific structural design. Establishing effective charge transfer pathways such as through-bond pathways, extended conjugated pathways, and through-space pathways. Constructing π···d conjugated planes and π···π stacking pathways, two-dimensional MOFs can dominate in conductive MOFs, which plays a vital role in the preparation of conductive MOFs. Therefore, the electrochemical applications of MOFs as conductive materials have been greatly expanded.

[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0006] The first object of the present invention is to provide a Cu(I) conductive coordination polymer, which has readily available raw materials, a simple preparation method, high yield, a small band gap and good thermal stability. The complex is used as a semiconductor material. At room temperature, the conductivity of complexes 1 and 2 is 2.18×10 -4 Scm-1 and 5.85×10 -6 Scm -1 As the temperature increases, at 100°C, the conductivity of complex 1 and complex 2 are 1.01×10 -2 Scm -1 and 8.76×10 -5 Scm -1 , the efficient conductivity performance has broad application prospects.

[0007] The above technical objectives of the present invention are achieved through the following technical solutions:

[0008] A Cu(I) conductive coordination polymer material, wherein a Cu(I) complex is used as a semiconductor material and is prepared by using CuBr or CuI and pytrz; pytrz is 3-(4H-1,2,4-triazole-4-yl)pyridine;

[0009] Wherein, CuBr and pytrz are used to prepare complex 1, and the structural molecular formula of complex 1 is [CuBr(pytrz)2] n ; CuI and pytrz are used to prepare complex 2, the structural formula of which is [Cu2I2(pytrz)] n ; Complexes 1 and 2 crystallize in the triclinic P-1 space group.

[0010] The unit cell parameters of complex 1 are α=77.263(5)°, β=83.520(5)°, γ=66.825(5)°, Z=2,

[0011] The crystal parameters of complex 2 are α=90°, β=83.520(5)°, γ=90°, Z=2,

[0012] The asymmetric unit of complex 1 consists of a four-coordinated Cu center connected to three different N atoms of pytrz ligands and a Br anion. Pytrz acts as a bridging ligand to connect the metal units to form a one-dimensional chain structure. There are two π···π stacking interactions between the aromatic rings of Pytrz between the two almost parallel chains. The center-to-center distances of the aromatic planes from A to B and from C to D are 3.9383A and 3.7454A, respectively. This structure provides a pathway for the transfer of electrons, allowing the charge to be transferred between the Cu–N bonds through localization, that is, through the interaction between the π electron system in the ligand and the d orbital of the metal Cu, forming an effective charge transfer channel; it facilitates the migration of charges between the two-dimensional layers, further improving the conductivity. Especially at higher temperatures, thermal vibrations in the chain can further promote the migration of charges, thereby improving the conductivity.

[0013] In the structure of complex 2, the Cu2I2 units are interconnected to form a double-stranded ladder extending along the crystallographic a-axis, and the pytrz ligand is connected to [CuI] n The copper iodide ribbon is stacked along both sides of the copper iodide skeleton and extends along the crystallographic b-axis to form a two-dimensional plane. The Cu-I chain segments in this double-chain structure provide a charge conduction path along the a-axis, while the two-dimensional planar structure formed by the Pytrz ligand connecting the Cu-I chain enhances the orbital interaction between Cu and I, promotes the spatial transport of charges, and enables the charges to migrate in multiple directions (a-axis and b-axis), thus enhancing the overall conductivity.

[0014] Furthermore, at room temperature, the conductivity of complex 1 and complex 2 are 2.18×10 -4 Scm -1 and 5.85×10 -6 Scm -1 As the temperature increases, at 100°C, the conductivity of complex 1 and complex 2 are 1.01×10 - 2 Scm -1 and 8.76×10 -5 Scm -1 .

[0015] The second object of the present invention is to provide a method for preparing a Cu(I) conductive coordination polymer, which can efficiently construct a ligand pytrz having a 1,2,4-triazole group and a pyridine structure, wherein both the triazole ring and the pyridine ring are conjugated aromatic structures, and can provide an effective charge delocalization transfer pathway. This enables the ligand to form a good charge transfer network when subsequently coordinating with metal Cu(I), thereby improving the conductivity of the complex.

[0016] The above technical objectives of the present invention are achieved through the following technical solutions:

[0017] A method for preparing a Cu(Ⅰ) conductive coordination polymer material, comprising:

[0018] Preparation of organic ligand pytrz: Under the protection of inert gas, 3-amino-pyridine and N,N'-bis(dimethylaminomethylene)hydrazine are placed in a flask, p-toluenesulfonic acid monohydrate and xylene are added, and the mixture is stirred, heated and refluxed for 24 hours. After the reaction is completed, the xylene is poured out, and the residue is washed with petroleum ether to remove the N,N-bis(dimethylaminomethylene)hydrazine therein. Dichloromethane is added to the remaining solid until it is just dissolved, and then the same volume of petroleum ether is added to recrystallize at low temperature to obtain a pure needle-shaped solid, which is the organic ligand pytrz;

[0019] Among them, p-toluenesulfonic acid monohydrate is used as a catalyst to promote the reaction. Xylene is a high-boiling point solvent. During the 24-hour heating reflux, it provides a stable reaction environment so that the reactants can fully react. The reflux reaction is carried out at a high temperature of 160°C to 162°C. The nitrogen atom in N,N'-bis(dimethylaminomethylene)hydrazine undergoes a condensation reaction with the amino group of 3-aminopyridine to form a 1,2,4-triazole ring structure, and the pyridine group is retained in the structure. Finally, the desired organic ligand pytrz-3-(4H-1,2,4-triazol-4-yl)pyridine is formed. Through the recrystallization step, the final pytrz is a pure needle-shaped solid, ensuring its chemical stability and reactivity in subsequent applications.

[0020] Preparation of complex 1[CuBr(pytrz)2] n : Pytrz and CuBr are added to acetonitrile solvent and stirred respectively. After stirring, the mixture is filtered to obtain a mixed solution. The mixed solution is sealed with plastic wrap in a beaker and pierced with holes. The mixed solution is allowed to stand at room temperature to evaporate, and bright yellow crystals suitable for X-ray diffraction analysis are precipitated. The obtained crystals are filtered, washed with acetonitrile, and dried in air to obtain pure bright yellow crystals, which are the organic complex [CuBr(pytrz)2]. n ;

[0021] Preparation of complex 2[Cu2I2(pytrz)] n :Pytrz and CuI are added to acetonitrile solvent and stirred. After stirring, the mixed solution is filtered to obtain a mixed solution. The mixed solution is sealed with plastic wrap in a beaker and pierced with holes. The mixed solution is allowed to stand at room temperature to evaporate and yellow crystals suitable for X-ray diffraction analysis are precipitated. The obtained crystals are filtered, washed with acetonitrile, and dried in air to obtain pure yellow crystals, which are the organic complex [Cu2I2(pytrz)] n .

[0022] Furthermore, in the preparation of the organic ligand pytrz, the molar ratio of 3-amino-pyridine, N,N'-bis(dimethylaminomethylene)hydrazine, and p-toluenesulfonic acid monohydrate is 74.4-75.1:163.6-164.1:7.0-7.21; the volume of the xylene solvent is 80mL-85mL. The time of heating and stirring treatment is 23h-24h; the time of reflux heating treatment is 23h-24h to ensure the full progress of the reaction, and the reflux heating temperature is 160℃-162℃. In the preparation of the organic ligand pytrz, the proportion of raw materials is excessive to make the reaction sufficient; the product has many impurities when the amount of xylene is small; the boiling point of xylene is 160℃, and condensation reflux can only be carried out at this temperature.

[0023] Furthermore, in complex 1[CuBr(pytrz)2] n In the preparation of the complex 2[Cu2I2(pytrz)], the molar ratio of CuBr to pytrz is 0.09-0.11:0.09-0.11, and the volume of the acetonitrile solvent is 20ml-22ml. n In the preparation, the molar ratio of CuI and pytrz is 0.09-0.11:0.09-0.11; the volume of acetonitrile solvent is 20ml-22ml. If the ratio of drug to solvent is too large, precipitation and floccules are easily formed during the reaction, and if the ratio is small, precipitation is formed without growing crystals.

[0024] Furthermore, the reaction conditions for static volatilization are: volatilization temperature is 15° C. to 25° C., and reaction time is 1.5 to 2.5 days.

[0025] The third object of the present invention is to provide an application method of Cu(I) conductive coordination polymer. The complex can be used as a semiconductor material in the fields of electrochemical sensors, electronic devices, conductive films, etc. At room temperature, the conductivity of complexes 1 and 2 is 2.18×10 -4 Scm -1 and 5.85×10 -6 Scm -1 As the temperature increases, at 100°C, the conductivity of complex 1 and complex 2 are 1.01×10 -2 Scm -1 and 8.76×10 -5 Scm -1 . , the high efficiency conductivity performance has broad application prospects.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The one-dimensional chain structure in complex 1 connects the Cu(I) metal centers through the pytrz ligand, forming an effective charge transfer path. In particular, through the bonding of Cu–N and Cu–Br, the charge can move along the chain direction to achieve efficient charge transport. The double-chain Cu2I2 structure in complex 2 provides a more multidimensional charge conduction pathway. With the bridging effect of the pytrz ligand, the charge can be transferred between two-dimensional layers. The Cu(I) complex provided by the present invention is used as a semiconductor to measure the temperature-dependent conductivity by AC impedance, showing efficient conductivity performance.

[0028] (2) In the present invention, both complex 1 and complex 2 form a stable crystal structure. This orderly arrangement makes the charge transfer more efficient, and the stability of the crystal structure ensures that the performance of the material is not easily attenuated at high temperatures, and has good thermal stability. The preparation method of the material is completed at room temperature and pressure, and the synthesis steps are simplified, the reaction conditions are mild, the reaction product is pure, and the yield is high, thereby reducing the production cost.

[0029] (3) At room temperature, the electrical conductivities of complex 1 and complex 2 are 2.18×10 -4 Scm -1 and 5.85×10 - 6 Scm -1 As the temperature rises to 100°C, the conductivity of complex 1 increases to 1.01×10 -2 Scm -1 , complex 2 increased to 8.76×10 -5 Scm -1 , showing a positive effect of temperature on conductivity, with excellent thermal stability, and suitable for application in electronic devices and sensors in high temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 (a) is the X-ray crystal structure of complex 1; (b) is the X-ray crystal structure of complex 2; hydrogen atoms are omitted;

[0032] Figure 2 is the two-dimensional structure of the X-ray crystal of complex 1; hydrogen atoms are omitted;

[0033] Figure 3 is the infrared spectrum of complex 1 and organic ligand pytrz;

[0034] Figure 4 is the infrared spectrum of complex 2 and organic ligand pytrz;

[0035] Figure 5 is the powder X-ray diffraction pattern of complex 1;

[0036] Figure 6 is the powder X-ray diffraction pattern of complex 2;

[0037] Figure 7 is the thermogravimetric diagram of complex 1;

[0038] Figure 8 is the thermogravimetric diagram of complex 2;

[0039] Fig. 9 is the UV-visible absorption spectra of complex 1 and complex 2;

[0040] Fig.10 is the Tauc plot of complex 1 and complex 2;

[0041] Fig.11 is the fluorescence excitation and emission spectra of complex 1;

[0042] Fig.12 is the fluorescence excitation and emission spectra of complex 2;

[0043] Fig.13 is the photoluminescence quantum efficiency of complex 1 measured at 298K;

[0044] Fig.14 is the photoluminescence quantum efficiency of complex 2 measured at 298K;

[0045] Fig.15 PL lifetime decay curves of complex 1 and complex 2;

[0046] Fig.16 is the temperature-dependent photoluminescence spectrum of complex 1;

[0047] Fig.17 is the temperature-dependent photoluminescence spectrum of complex 2;

[0048] Fig.18 The transient photocurrent response diagrams of complex 1 and complex 2;

[0049] Fig.19 is the variable temperature Nyquist plot of complex 1;

[0050] Fig. 20 is the variable temperature Nyquist plot of complex 2;

[0051] Fig.21 is the fitted Nyquist plot of complex 1;

[0052] Fig. 22 is the fitted Nyquist plot of complex 2;

[0053] Fig.23 is the temperature-dependent conductivity of the complex. DETAILED DESCRIPTION

[0054] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a Cu (I) conductive coordination polymer material and its preparation and application method proposed by the present invention, its specific implementation method, characteristics and effects are described in detail as follows. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0055] The first aspect of the present invention provides a Cu(Ⅰ) conductive coordination polymer material, such as Figure 1 As shown in (a), the single crystal structure formula of the material is: Complex 1[CuBr(pytrz)2] n ; Wherein, pytrz is 3-(4H-1,2,4-triazol-4-yl)pyridine. Complex 1 crystallizes in the triclinic system P-1 space group, and the crystal parameters of complex 1 are α=87.841(3), β=72.121(4), γ=69.733(4), Z=2, like Figure 2 As shown in the figure, the two-dimensional structure of complex 1 shows that there are two π···π stacking interactions between the aromatic rings of Pytrz between two almost parallel chains. The distances from the center of mass to the center of mass of the aromatic planes from A to B and from C to D are 3.9383A and 3.7454A, respectively. This structure provides a pathway for the transfer of electrons, allowing the charge to be transferred between the Cu–N bonds through localization, that is, through the interaction between the π electron system in the ligand and the d orbital of the metal Cu, forming an effective charge transfer channel; it helps the charge migration between the two-dimensional layers, further improving the conductivity. Especially at higher temperatures, thermal vibrations in the chain can further promote the migration of charges, thereby improving the conductivity.

[0056] like Figure 1 As shown in (b), the structural formula of complex 2 is [Cu2I2(pytrz)] n ; wherein pytrz is 3-(4H-1,2,4-triazol-4-yl)pyridine. The crystal parameters of complex 2 are α=90°, β=83.520(5)°, γ=90°, Z=2, In the material, the asymmetric unit is composed of two crystallographically independent Cu(I) and the ligand pytrz. Specifically, the complex is characterized by a two-dimensional (2D) MOF assembled by connecting Cu2I2 and pytrz. In the structure of complex 2, the Cu2I2 units are connected to each other to form a double-chain ladder extending along the crystallographic a-axis. The pytrz ligand connects [CuI] n The copper iodide ribbon is stacked along both sides of the copper iodide skeleton and extends along the crystallographic b-axis to form a two-dimensional plane. The Cu-I chain segments in this double-chain structure provide a charge conduction path along the a-axis, while the two-dimensional planar structure formed by the Pytrz ligand connecting the Cu-I chain enhances the orbital interaction between Cu and I, promotes the spatial transport of charges, and enables the charges to migrate in multiple directions (a-axis and b-axis), thus enhancing the overall conductivity.

[0057] A second aspect of the present invention provides a method for preparing a Cu(I) conductive coordination polymer material, the method comprising:

[0058] S1. Preparation of organic ligand pytrz: Under the protection of inert gas, 3-amino-pyridine and N, N'-bis (dimethylaminomethylene) hydrazine are placed in a flask, p-toluenesulfonic acid monohydrate and xylene are added, and heated to reflux for 24 hours. After the reaction is completed, the xylene is poured out, and the residue is washed with petroleum ether to remove the N, N-bis (dimethylaminomethylene) hydrazine therein, and the remaining solid is added with dichloromethane until it is just dissolved, and then the same volume of petroleum ether is added to recrystallize at low temperature to obtain a pure needle-shaped solid, which is the organic ligand pytrz.

[0059] S2. Preparation of organic complex 1 [CuBr(pytrz)2] n : Pytrz and CuBr are added to acetonitrile solvent and stirred respectively. After stirring, the mixture is filtered to obtain a mixed solution. The mixed solution is sealed and pierced in a beaker. The mixed solution is allowed to stand at room temperature to evaporate and wait for the precipitation of bright yellow crystals suitable for X-ray diffraction analysis. The obtained crystals are filtered, washed with acetonitrile, and dried in air to obtain pure bright yellow crystals, which are the organic complex [CuBr(pytrz)2]. n .

[0060] S3. Preparation of complex 2 [Cu2I2(pytrz)] n The synthesis method of complex 2 is similar to that of complex 1, except that CuBr is replaced by CuI. The yellow crystal is the organic complex [Cu2I2(pytrz)] n The preparation method has readily available raw materials, a simple synthesis method, a high yield, and has the same technical effect.

[0061] The reagents involved in the experiment were from manufacturers such as Anage Chemical, Alfa Reagent and Sinopharm Group, and the details are shown in Table 1; the reagents involved were used directly without further purification.

[0062] Table 1 Reagents

[0063]

[0064]

[0065] The equipment and instruments used in the experiment are shown in Table 2:

[0066] Table 2 Main instruments

[0067]

[0068] Example 1

[0069] The present invention provides a method for preparing a Cu(I) conductive coordination polymer material, which comprises a single crystal structure, wherein the molecular formula of the single crystal structure of the complex material is: the structural molecular formula of the complex 1 is [CuBr(pytrz)2] n ; The structural formula of complex 2 is [Cu2I2(pytrz)] n ; wherein pytrz is 3-(4H-1,2,4-triazol-4-yl)pyridine.

[0070] Crystals prepared by solvothermal method were collected under microscope, and crystallographic data of the complex were acquired on a Bruker APEX-IICCD instrument with graphene monochromatic radiation. The data were collected at the corresponding temperature. The data collection, data reduction and unit optimization were performed using two program packages, Bruker Instrument Service v4.2.2 and SAINT V8.34A. The structure of the complex was solved using the SHELXS program package, and the crystal data were optimized using the full matrix least squares method using the SHELXL program package. Absorption correction was performed using the multi-scan program package SADABS. The hydrogen atoms of the organic ligands were analyzed using the riding mode on the SHELXTL program package. 2 The crystallographic data of the complex are shown in Table 3. The bond lengths of some of the complexes are The data of bond angle (°) are shown in Table 4.

[0071] Table 3 Crystallographic parameters of the complexes

[0072]

[0073] a R1=Σ(||F0|-|Fc ||) / Σ|F0|; b wR2=[Σw(|F0 2 |-|F c 2 |) 2 / Σw|F0 2 | 2 ] 1 / 2 ; c GOF=[∑[w(F0 2 -F c 2 )

[0074] 2 ] / (N obs -N params )] 1 / 2 ,

[0075] Based on the data I>2σ(I).

[0076] Table 4 Important bond lengths in the complex crystal structure and bond angle (°)

[0077]

[0078]

[0079] Example 2

[0080] Preparation of organic ligand pytrz: Under the protection of inert gas, 3-amino-pyridine (7.06g, 74.4mmol) and N, N'-bis (dimethylaminomethylene) hydrazine (23.23g, 163.6mmol) were placed in a flask, p-toluenesulfonic acid monohydrate (1.33g, 7.0mmol) and 80.0mL of xylene were added, and heated to reflux for 24h. After the reaction, the xylene was poured out, and the residue was washed with petroleum ether to remove N, N'-bis (dimethylaminomethylene) hydrazine. The remaining solid was added with dichloromethane until it was well dissolved, and then the same volume of petroleum ether was added to recrystallize at low temperature to obtain a pure needle-shaped solid, namely 3- (4H-1,2,4-triazol-4-yl) pyridine. Yield: 80%.

[0081] Example 3

[0082] Complex 1[CuBr(pytrz)2] nPreparation: Pytrz (14.6 mg, 0.1 mmol) and CuBr (19.0 mg, 0.1 mmol) were added to a 100 ml beaker of acetonitrile (20 mL) and stirred. After stirring, the mixture was filtered to obtain a mixed solution. The mixed solution was sealed with plastic wrap in the beaker and pierced with holes. The mixture was allowed to stand at room temperature for 2 days to evaporate. Bright yellow crystals suitable for X-ray diffraction analysis were precipitated. The obtained crystals were filtered, washed with acetonitrile, and dried in air to obtain pure bright yellow crystals, which were the organic complex [CuBr(pytrz)2]. n , yield: 75%.

[0083] Complex 2[Cu2I2(pytrz)] n Preparation: Pytrz (14.6 mg, 0.1 mmol) and CuI (14.3 mg, 0.1 mmol) were added to a 100 ml beaker of acetonitrile (20 mL) and stirred. After stirring, the mixture was filtered to obtain a mixed solution. The mixed solution was sealed with plastic wrap in the beaker and pierced with holes. The mixture was allowed to stand at room temperature for 2 days to evaporate. Bright yellow crystals suitable for X-ray diffraction analysis were precipitated. The obtained crystals were filtered, washed with acetonitrile, and dried in air to obtain pure bright yellow crystals, which are the organic complex [Cu2I2(pytrz)]. n , yield: 64%.

[0084] Example 4

[0085] Infrared absorption spectroscopy analysis: Figure 3 and Figure 4 As shown in the figure, the black line is the infrared absorption spectrum of the ligand pytrz, and the red line is the infrared absorption spectrum of the complex. From this figure, it can be seen that the absorption spectra of complexes 1 and 2 are very consistent with the absorption spectrum of the ligand, indicating that there is indeed an organic ligand in the complex.

[0086] Example 5

[0087] Powder X-ray diffraction analysis: Figure 5 and Figure 6 As shown in the figure, the black spectrum is drawn from the experimental data, and the red spectrum is obtained by computer simulation based on the crystal structure. From this figure, it can be seen that the experimental values ​​and simulation values ​​of complexes 1 and 2 are very consistent, indicating that the complex is pure phase.

[0088] Example 6

[0089] Thermogravimetric analysis: Figure 7 and Figure 8As shown, the thermal stability of complex 1 and complex 2 was studied by thermogravimetric analysis (TGA). From the TGA curve, it can be seen that the initial decomposition temperatures of complex 1 and complex 2 are 230°C and 280°C, respectively, indicating that the complexes have high thermal stability.

[0090] Example 7

[0091] UV-Vis Diffuse Reflectance Spectroscopy Analysis: UV-Vis Diffuse Reflectance Spectroscopy (DRS) was performed on complexes 1 and 2 to study the optical properties of the complexes, such as Fig. 9 As shown, both complexes exhibit obvious broad absorption peaks, and in complex 1, there is an obvious absorption peak in the low energy region. The Tauc equation is used to evaluate the optical properties of the materials, especially their band gaps, as shown in Fig.10 As shown in the figure, the band gap energy (E g ) are 1.26 eV and 2.06 eV, respectively, indicating the semiconductor properties of complex 1 and complex 2. According to calculations, complex 1 is a direct semiconductor and complex 2 is an indirect semiconductor.

[0092] Example 8

[0093] Fluorescence test: Fig.11 and Fig.12 As shown, complex 1 exhibits a strong emission band centered at 575 nm with a half-peak width (FWHM) of about 136 nm, and complex 2 exhibits a strong emission band centered at 565 nm with a half-peak width (FWHM) of about 128 nm. Fig.13 and Fig.14 As shown, the photoluminescence quantum yields (PLQY) of complex 1 and complex 2 in the solid state are 18.00% and 40.96%, respectively. Fig.15 The photoluminescence (PL) decay curve is shown. The PL lifetimes of complex 1 and complex 2 are 3.54μs and 1.04μs, respectively. The solid-state photophysical data of the complex at room temperature are shown in Table 5. The fluorescence decay rate (k r )(k r =Φ PL τ -1 ) were 5.08×10 4 s -1 and 39.38×10 4 s -1 Considering Φ PL =k r / (k r +k nr ), where k nr is the rate of the nonradiative process including nonradiative singlet decay and ISC, k of the complex nrThe estimated values ​​are 2.32×10 5 s -1 and 5.68×10 5 s -1 .

[0094] Table 5 Solid-state photophysical data of the complexes at room temperature

[0095]

[0096] a Radiative rate constant calculated K r =Φ / τ. b Nonradiative rateconstant calculated K nr =(1-Φ) / τ.

[0097] Example 9

[0098] Temperature-dependent photoluminescence spectroscopy analysis: Fig.16 and Fig.17 As shown in the figure, in the temperature-dependent (TD) emission spectra, complexes 1 and 2 have similar luminescence temperature dependence, both of which show thermal quenching effects, and the temperature-related emission changes of complexes 1 and 2 are slightly different. As the temperature gradually increases from 80K to 500K, the emission center of complex 1 shows a small blue shift of about 10nm, and the emission center of complex 2 shows a larger blue shift (ca: 20nm).

[0099] Example 10

[0100] Electrochemical experiment: The complex (5 mg) was dispersed in a mixed solution of 25 μL Nafion, 75 μL H2O and 150 μL CH3CH2OH, and the sample was prepared by ultrasonication for 20 minutes. The test system was a three-electrode system, the sample was evenly dropped on the electrode, and after drying, it was used as the working electrode, the reference electrode was an Ag / AgCl electrode, the counter electrode was a platinum rod electrode, and the electrolyte was a 0.1M sodium sulfate solution, and the test was performed on an electrochemical workstation.

[0101] The photoelectric conversion of the complex was studied and the transient photocurrent response of the complex was recorded, such as Fig.18 As shown in Figure 1, since the photogenerated electron-hole pairs in the complex cannot recombine immediately after the light is removed, the current slowly decreases after the light source is removed. In contrast, the photocurrent density of complex 1 is stronger than that of complex 2.

[0102] Embodiment 11

[0103] The variable temperature Nyquist plot of the complex is as follows: Fig.19 and Fig. 20 As shown, the synthesized crystal powder sample (L = 0.40mm, d = 4.00mm) was subjected to AC impedance measurement, and the impedance data was studied as a function of temperature. From 30°C to 100°C, the temperature-dependent impedance of complex 1 and complex 2 was measured, and the corresponding Nyquist plots were displayed. The Nyquist plots at different temperatures were fitted according to the literature references, as shown in FIG. Fig.21 is the fitted spectrum of complex 1 at different temperatures, Fig. 22 It is the fitting spectrum of complex 2 at different temperatures, and the inset is the equivalent circuit.

[0104] Example 12

[0105] The temperature-dependent conductivity of the complex, such as Fig.23 As shown, the Nyquist plot has a semicircle in the high-frequency region, indicating the bulk resistance of the material, and a tail in the low-frequency region. The bulk conductivity is determined by the semicircle in the Nyquist plot. The resistance R is obtained by fitting the Nyquist plot data. The calculation formula for conductivity is δ = L / RS. At room temperature, the conductivity of complex 1 and complex 2 are 2.18×10 -4 Scm -1 and 5.85×10 -6 S cm -1 As the temperature increases, at 100°C, the conductivity of complex 1 and complex 2 are 1.01×10 -2 Scm -1 and 8.76×10 -5 Scm -1 In contrast, the conductivity of complex 1 is 10 times that of complex 2. 2 The π···π stacking interaction between the aromatic rings of the PyTRZ ligands in the structure of complex 1 leads to an increase in charge transport, thereby improving the conductivity.

[0106] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A Cu(I) conductive coordination polymer material, characterized in that: The Cu(I) complex is used as a semiconductor material and is prepared by using CuBr or CuI and pytrz; the pytrz is 3-(4H-1,2,4-triazol-4-yl)pyridine; Wherein, the CuBr and pytrz are used to prepare complex 1, and the structural molecular formula of complex 1 is [CuBr(pytrz)2] n The CuI and pytrz are used to prepare complex 2, the structural formula of which is [Cu2I2(pytrz)] n ; The complex 1 and the complex 2 crystallize in the triclinic P-1 space group.

2. A Cu(I) conductive coordination polymer material according to claim 1, characterized in that: The unit cell parameters of the complex 1 are a = 7.2584(4) Å, b = 9.1745(5) Å, c = 9.6276(6) Å, α = 77.263(5)°, β =83.520(5)°, γ = 66.825(5)°, Z = 2, V = 574.64(6) Å 3 .

3. A Cu(I) conductive coordination polymer material according to claim 1, characterized in that: The crystal parameters of complex 2 are a = 7.2584(4) Å, b = 9.1745(5) Å, c = 9.6276(6) Å, α = 90°, β = 83.520(5)°, γ = 90°, Z = 2, V = 574.64(6) Å 3 .

4. The Cu(I) conductive coordination polymer material according to claim 2, characterized in that: The asymmetric unit of the complex 1 consists of a four-coordinated Cu center connected to three N atoms of different pytrz ligands and a Br anion; Pytrz acts as a bridging ligand to connect the metal units to form a one-dimensional chain structure.

5. The Cu(I) conductive coordination polymer material according to claim 3, characterized in that: In the structure of complex 2, Cu2I2 are interconnected to form a double-chain ladder extending along the crystallographic a-axis, and the pytrz segment connects [CuI] n ribbons, stacked along both sides of the copper iodide skeleton, extending along the crystallographic b-axis to form a two-dimensional plane.

6. A method for preparing a Cu(I) conductive coordination polymer material according to any one of claims 1 to 5, characterized in that: include: Preparation of organic ligand pytrz: under the protection of inert gas, 3-amino-pyridine and N,N'-bis(dimethylaminomethylene)hydrazine are placed in a flask, p-toluenesulfonic acid monohydrate and xylene are added, stirred and heated to reflux; after the reaction is completed, xylene is poured out, and the residue is washed with petroleum ether to remove N,N-bis(dimethylaminomethylene)hydrazine therein, and dichloromethane is added to the remaining solid until it is just dissolved, and then the same volume of petroleum ether is added to recrystallize at low temperature to obtain a pure needle-shaped solid, which is the organic ligand pytrz; Preparation of complex 1 [CuBr(pytrz)2] n : Pytrz and CuBr are added to acetonitrile solvent respectively and stirred. After stirring, the mixture is filtered to obtain a mixed solution. The mixed solution is sealed with plastic wrap in a beaker and pierced with holes. The mixed solution is allowed to stand at room temperature for evaporation, and bright yellow crystals suitable for X-ray diffraction analysis are precipitated. The obtained crystals are filtered, washed with acetonitrile, and dried in air to obtain pure bright yellow crystals, which are the organic complex [CuBr(pytrz)2]. n ; Preparation of complex 2 [Cu2I2(pytrz)] n : Pytrz and CuI are added to acetonitrile solvent respectively and stirred. After stirring, the mixed solution is filtered to obtain a mixed solution. The mixed solution is sealed with plastic wrap in a beaker and pierced with holes. The mixed solution is allowed to stand at room temperature for evaporation, and yellow crystals suitable for X-ray diffraction analysis are precipitated. The obtained crystals are filtered, washed with acetonitrile, and dried in air to obtain pure yellow crystals, which are the organic complex [Cu2I2(pytrz)] n .

7. The method for preparing a Cu(I) conductive coordination polymer material according to claim 6, characterized in that: In the preparation of the organic ligand pytrz, the molar ratio of 3-aminopyridine, N,N'-bis(dimethylaminomethylene)hydrazine, and p-toluenesulfonic acid monohydrate is 74.4 ~ 75.1:163.6 ~ 164.1:7.0 ~ 7.21; the volume of the xylene solvent is 80 mL ~ 85 mL; the heating and stirring treatment time is 23 h ~ 24 h; the heating reflux time is 23 h ~ 24 h, and the heating reflux temperature is 160°C ~ 162°C.

8. The method for preparing a Cu(I) conductive coordination polymer material according to claim 6, characterized in that: The molar ratio of CuBr to pytrz is 0.09 ~ 0.11: 0.09 ~ 0.11, and the molar ratio of CuI to pytrz is 0.09 ~ 0.11: 0.09 ~ 0.11; the volume of the acetonitrile solvent is 20 ml ~ 22 ml.

9. The method for preparing a Cu(I) conductive coordination polymer material according to claim 4, characterized in that: The reaction conditions of the static volatilization are: the volatilization temperature is 15°C to 25°C, and the reaction time is 1.5 to 2.5 days.

10. Use of the Cu(I) conductive coordination polymer material according to any one of claims 1 to 3 as a semiconductor in electrochemistry.

Citation Information

Cited By

  • Copper-based coordination polymer, preparation method thereof and application of copper-based coordination polymer in synergistic effect of nitrogen fertilizer

    CN121609930A